PROSES ISLAMISASI DALAM RITUAL KHANDURI BLANG DI GAMPONG DAYAH LEUBUE KECAMATAN ULIM KABUPATEN PIDIE JAYA - Nurazizah, Nurazizah; Riza, Faisal; Fernanda Desky, Ahmed (CV. Kalimasada Group, 2023)
This study aims to find out how the process of Islamization in khanduri blang, which was previously carried out at the tomb of the ulama, became a meunasah and also to find out what social changes took place in society during the process of Islamization in khanduri blang ritual in Gampong Dayah Leubue, Ulim District, Pidie Jaya Regency. This research is a field research that uses qualitative research methods with descriptive research types that come into direct contact with informants by conducting interviews and direct observation. The results of this study explain that the process of Islamization in the khanduri blang ritual is caused by two factors, namely the will of the community itself and the existence of da'wah and education channels that make a difference and change in the implementation of the khanduri blang ritual in Gampong Dayah Leubue. In addition, this process of Islamization is closely related to August Comte's theory of 3 stages of development, namely the theological stage where people still believe in supernatural things such as performing rituals at the tombs of the clergy, then the metaphysical stage where the farming community believes. prohibited from going down to the rice fields for 3 days, and a positive stage where people already have progress and renewal of education and thoughts to abandon beliefs that according to them do not exist in Islamic teachings.